Economics of the Middle East development challenges - Devlin, Julia (World scientific lecture notes in economics ;, 2016)
This lecture note volume aims to introduce economic concepts and analysis to undergraduate level students, in the context of contemporary development challenges in the economics of the Middle East and North Africa (MENA).